Influence of micro-topography on the spatial heterogeneity of above-ground biomass: Lessons from the Qinglan Port Mangrove Nature Reserve, China - Meihuijuan Jiang; Penghua Qiu; Dezhi Wang; Minghui Wu; Ruiquan Lai; Xinqing Zou; Tingting Si; Hui Li; Qidong Shi; Yi Lin; Genzong Xie; Yanli Yang; et al. (Ecological Indicators)
Biomass is a crucial aspect of mangrove wetland ecosystems, intimately connected to biodiversity, carbon cycles, and habitat environment. It is influenced by micro-topography, which impacts local water heat distribution, and water and soil physical and chemical properties. Therefore, investigating the relationship between micro-topography and mangrove biomass has significant implications for the thorough protection and restoration of mangrove wetlands. This research focuses on the Bamen Bay area of the Qinglan Port Mangrove Nature Reserve in China’s Hainan Province. Using UAV LiDAR point cloud and high-resolution orthophotos, we identified the study area’s micro-topography types and divided it into five tidal zones. We employed the random forest algorithm to map the spatial distribution of mangrove above-ground biomass (AGB), and used geographic detectors and structural equation model (SEM) to study micro-topography’s impact on AGB spatial differentiation. We found: (1) The area has 15 distinct micro-topography types; seven of these – underwater shoal, sandbar, mangrove tidal flat, lagoon plain, delta, marine-alluvial plain, and marine plain – cover larger areas. (2) The mangrove area totals 781.93 ha, with plants mainly growing in low and mid-tidal zones, dominated by species or genus like Sonneratia spp., Bruguiera sexangula, Lumnitzera racemosa, Caryophyllaceae, and Rhizophora spp.. (3) The average AGB in the study area is 151.36 Mg/ha. Different tidal zones have significantly different mangrove AGB; the AGB of low and mid-tidal zones constitute 38.71 % and 52.68 % of the total area’s AGB, respectively. (4) Individually, micro-topography or water and soil physical and chemical characteristics do not significantly impact mangrove AGB at different tidal zones. However, in combination, they significantly enhance mangrove AGB. (5) According to the SEM, water and soil physical and chemical properties directly impact mangrove AGB significantly (impact values being 0.54 and 0.29 respectively). Micro-topography type has a lesser positive impact on mangrove AGB (0.02), and elevation has a significant positive impact (0.18). Yet, micro-topography type and elevation indirectly influence AGB’s spatial differentiation more through their effects on the water and soil environments. This study reveals the relationship between micro-topography and mangrove AGB, providing crucial scientific support for the targeted protection and restoration of mangrove wetlands.